Influenza A Virus Surveillance Based on Pre‐Weaning Piglet Oral Fluid Samples. Issue 5 (9th December 2014) - Panyasing, Y.; Goodell, C.; Kittawornrat, A.; Wang, C.; Levis, I.; Desfresne, L.; Rauh, R.; Gauger, P. C.; Zhang, J.; Lin, X.; Azeem, S.; Ghorbani‐Nezami, S.; et al.
Summary: Influenza A virus (IAV) surveillance using pre‐weaning oral fluid samples from litters of piglets was evaluated in four ˜ 12 500 sow and IAV‐vaccinated, breeding herds. Oral fluid samples were collected from 600 litters and serum samples from their dams at weaning. Litter oral fluid samples were tested for IAV by virus isolation, quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR), RT‐PCR subtyping and sequencing. Commercial nucleoprotein (NP) enzyme‐linked immunosorbent assay (ELISA) kits and NP isotype‐specific assays (IgM, IgA and IgG) were used to characterize NP antibody in litter oral fluid and sow serum. All litter oral fluid specimens ( n = 600) were negative by virus isolation. Twenty‐five oral fluid samples (25/600 = 4.2%) were qRT‐PCR positive based on screening (Laboratory 1) and confirmatory testing (Laboratory 2). No hemagglutinin (HA) and neuraminidase (NA) gene sequences were obtained, but matrix (M) gene sequences were obtained for all qRT‐PCR‐positive samples submitted for sequencing ( n = 18). Genetic analysis revealed that all M genes sequences were identical (GenBank accession no.KF487544 ) and belonged to the triple reassortant influenza A virus M gene (TRIG M) previously identified in swine. The proportion of IgM‐ and IgA‐positive samples was significantly higher in sow serum and litter oral fluid samples, respectively ( P < 0.01). Consistent with the extensive use of IAV vaccine, no difference was detected in the proportion of IgG‐ and blocking ELISA‐positive sow serum and litter oral fluids. This study supported the use of oral fluid sampling as a means of conducting IAV surveillance in pig populations and demonstrated the inapparent circulation of IAV in piglets. Future work on IAV oral fluid diagnostics should focus on improved procedures for virus isolation, subtyping and sequencing of HA and NA genes. The role of antibody in IAV surveillance remains to be elucidated, but longitudinal assessment of specific antibody has the potential to provide information regarding patterns of infection, vaccination status and herd immunity.